2011
DOI: 10.1021/jp2025939
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics and Mechanisms for Decomposition of Protonated Glycine and Its Protonated Dimer

Abstract: We present a full molecular description of fragmentation reactions of protonated glycine (G) and its protonated dimer, H(+)G(2), by studying their collision-induced dissociation (CID) with Xe using a guided ion beam tandem mass spectrometer (GIBMS). In contrast to previous results, it is clear that H(+)G decomposes by loss of CO followed by H(2)O. Analysis of the energy-dependent CID cross sections provides the 0 K barriers for these processes as well as for the binding energy of the dimer after accounting for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
44
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 81 publications
(165 reference statements)
12
44
0
Order By: Relevance
“…Finally, it can be seen that the cross section for reaction 8 declines at higher energies, which can be attributed to the decomposition of the H + G (y 1 ) product ion to form a 1 in the overall reaction 9b. This subsequent decomposition has been verified by the CID of H + G in a previous study [10]. In contrast to the current study, Klassen and Kebarle [2] observed only the major y 1 and a 1 channels with relative intensities that exhibit qualitatively the same behavior as that shown in Figure 1.…”
Section: Cross Sections For Collision-induced Dissociationsupporting
confidence: 85%
See 4 more Smart Citations
“…Finally, it can be seen that the cross section for reaction 8 declines at higher energies, which can be attributed to the decomposition of the H + G (y 1 ) product ion to form a 1 in the overall reaction 9b. This subsequent decomposition has been verified by the CID of H + G in a previous study [10]. In contrast to the current study, Klassen and Kebarle [2] observed only the major y 1 and a 1 channels with relative intensities that exhibit qualitatively the same behavior as that shown in Figure 1.…”
Section: Cross Sections For Collision-induced Dissociationsupporting
confidence: 85%
“…The ionic product from reaction 5, (CH 2 NH 2 + )(G), can also dissociate further according to reactions 6, 8, and 9a, where the former passes over a tight TS, Figure 5 of paper I, and the latter two channels involve loose TSs, Figure 1 of paper I. Finally, the y 1 (H + G) product of reaction 8 can dissociate to form the a 1 product ion in reaction 9b, as previously elucidated [10].…”
Section: Analysis Of Cross Sections For H + Gg Decomposition-primary mentioning
confidence: 53%
See 3 more Smart Citations